ANALISIS NILAI TAMBAH BERBAGAI PRODUK OLAHAN INDUSTRI RUMAH TANGGA BERBASIS BAHAN BAKU UBI KAYU DI KECAMATAN GERUNG KABUPATEN LOMBOK BARAT - Cici Ria Melani; Taslim Sjah; Bambang Dipokusumo (JURNAL AGRIMANSION, 2021)
This study aims to: (1) analyze the added value of processing business based on cassava raw material in Gerung District, West Lombok Regency, (2) analyze the benefit of processing business based on cassava raw material in Gerung District, West Lombok Regency, and (3) analyze the inhibiting factors of processing business based on cassava raw materials in Gerung District, West Lombok Regency. This research uses a descriptive method. The types of data used are quantitative and qualitative data. Sources of data used are primary data and secondary data. Data analysis using Hayami Method and profit analysis. The results showed that the added value was Rp. 9.571/kg (with a ratio of 67.79% and a profit rate of 80.33%) for cassava tape agroindustry, Rp. 18,191/kg (with a ratio of 71.34% and a profit rate of 88.20%) for cassava chips agroindustry, and Rp. 5.558/kg (with a ratio of 28% and a profit rate of 64.02%) for cassava pulp agroindustry. Profit of Rp. 384,782/production process and Rp. 10,389,114/month obtained from cassava tape agroindustry, Rp. 741,224/production process and Rp. 8,894,688/month obtained from cassava chips agroindustry, and Rp. 53,377/production process and Rp. 1,281,048/month obtained from cassava pulp agroindustry; and The inhibiting factors faced by processed entrepreneurs based on cassava raw materials in Gerung District, West Lombok Regency are the lack of raw material availability and limited working capital.